Green Public Procurement (GPP) sebagai Salah Satu Strategi SDGs untuk Mendukung Tata Kelola Pengadaan yang Ramah Lingkungan - Vina Valentina; Muhammad Adrian Perdana (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Green Public Procurement (GPP) is an approach to public procurement that takes environmental considerations into account in the planning, selection, and implementation stages of contracts. The goal is to ensure that the goods, services, or construction works selected not only meet the government's needs but also have a positive impact or at least minimal negative impact on the environment. Sustainable Development (SDGs) is a development concept that focuses on meeting the needs of the present without compromising the ability of future generations to meet their own needs, taking into account three pillars: economic growth, social aspects, and environmental aspects. The SDGs represent a global agenda aimed at addressing key challenges in global development, with a focus on achieving a harmonious balance between economic growth, social welfare, and environmental preservation. The SDGs consist of a series of targets designed to create inclusive, fair, and sustainable development, benefiting both the current and future generations. The success of GPP is strongly influenced by a strong commitment, clear regulations, capacity building of human resources, and synergy between the government, suppliers, and society. The use of information technology also plays a crucial role in ensuring transparency and efficiency in the implementation of GPP. Therefore, GPP plays a significant role as a catalyst for systemic change towards sustainable consumption and production patterns, while accelerating the achievement of global sustainable development goals.